The Paraventricular Nucleus of the Thalamus as an Integrating and Relay Node in the Brain Anxiety Network - Kirouac, Gilbert J. (Frontiers in Behavioral Neuroscience, 2021)
The brain anxiety network is composed of a number of interconnected cortical regions that detect threats and execute appropriate defensive responses via projections to the shell of the nucleus accumbens (NAcSh), dorsolateral region of the bed nucleus of the stria terminalis (BSTDL) and lateral region of the central nucleus of the amygdala (CeL). The paraventricular nucleus of the thalamus (PVT) is anatomically positioned to integrate threat- and arousal-related signals from cortex and hypothalamus and then relay these signals to neural circuits in the NAcSh, BSTDL and CeL that mediate defensive responses. This review describes the anatomical connections of the PVT that support the view that the PVT may be a critical node in the brain anxiety network. Experimental findings are reviewed showing that the arousal peptides orexins (hypocretins) act at the PVT to promote avoidance of potential threats especially following exposure of rats to a single episode of footshocks. Recent anatomical and experimental findings are discussed which show that neurons in the PVT provide divergent projections to subcortical regions that mediate defensive behaviors and that the projection to the NAcSh is critical for the enhanced social avoidance displayed in rats exposed to footshocks. A theoretical model is proposed for how the PVT integrates cortical and hypothalamic signals to modulate the behavioral responses associated with anxiety and other challenging situations.